Regulated RalBP1 binding to RalA and PSD-95 controls AMPA receptor endocytosis and LTD. - Kihoon Han; Myoung-Hwan Kim; Daniel Seeburg; Jinsoo Seo; Chiara Verpelli; Seungnam Han; Hye Sun Chung; Jaewon Ko; Hyun Woo Lee; Karam Kim; Won Do Heo; Tobias Meyer; et al. (PLoS Biology)
Long-term depression (LTD) is a long-lasting activity-dependent decrease in synaptic strength. NMDA receptor (NMDAR)-dependent LTD, an extensively studied form of LTD, involves the endocytosis of AMPA receptors (AMPARs) via protein dephosphorylation, but the underlying mechanism has remained unclear. We show here that a regulated interaction of the endocytic adaptor RalBP1 with two synaptic proteins, the small GTPase RalA and the postsynaptic scaffolding protein PSD-95, controls NMDAR-dependent AMPAR endocytosis during LTD. NMDAR activation stimulates RalA, which binds and translocates widespread RalBP1 to synapses. In addition, NMDAR activation dephosphorylates RalBP1, promoting the interaction of RalBP1 with PSD-95. These two regulated interactions are required for NMDAR-dependent AMPAR endocytosis and LTD and are sufficient to induce AMPAR endocytosis in the absence of NMDAR activation. RalA in the basal state, however, maintains surface AMPARs. We propose that NMDAR activation brings RalBP1 close to PSD-95 to promote the interaction of RalBP1-associated endocytic proteins with PSD-95-associated AMPARs. This suggests that scaffolding proteins at specialized cellular junctions can switch their function from maintenance to endocytosis of interacting membrane proteins in a regulated manner.